Enhanced Apoptosis of Monocytes from Complication-Free Juvenile-Onset Diabetes Mellitus Type 1 May Be Ameliorated by TNF-α Inhibitors - Jolanta Myśliwska; Monika Ryba-Stanisławowska; Marcin Smardzewski; Bartosz Słomiński; Małgorzata Myśliwiec; Janusz Siebert (Mediators of Inflammation)
Diabetes mellitus type 1 is associated with an enhanced apoptosis of different cells and tissues, accelerating occurrence of diabetic microvascular complications. The aim of our study was to determine spontaneous apoptotic potential of the monocyte subsets in juvenile-onset complication-free diabetes mellitus type 1 and to compare them with the corresponding values of the healthy. Moreover, we wanted to assess effects of TNF-R1 blocking agents and those of general TNF-α blocker (Infliximab) on spontaneous apoptosis of monocytes. Sixty randomly selected DM1 patients (14.5 ± 3.2 years) and 30 healthy (13.5 ± 2.8 years) volunteers were enrolled in the study. Our results indicate that three monocyte subsets are distinguishable in the groups of young diabetic patients and the healthy, similarly to in the blood of adults. DM1 patients were characterized by higher values of apoptotic monocytes than the healthy. The manipulation with drugs inhibiting TNF-R1 expression diminished the pool of CD16+ apoptotic monocytes. Infliximab reduced the apoptotic CD16− cells. In conclusion, diabetes mellitus type 1 is associated with greater apoptosis of three monocyte subsets which may contribute to the development of microvascular complications. TNF-α modifiers appear to ameliorate monocyte apoptosis. They may be useful for controlling excessive monocyte apoptosis in diabetic patients.